2019
DOI: 10.4103/aca.aca_2_18
|View full text |Cite
|
Sign up to set email alerts
|

Bioprosthetic valve thrombosis in carcinoid heart disease

Abstract: Tricuspid regurgitation in carcinoid syndrome leads to significant morbidity and mortality that may warrant a tricuspid valve replacement. However, for patients with high serotonin levels and known hypercoagulable risks, the optimum timing for surgery and postoperative anticoagulation approaches remain unclear. High serotonin-triggered hypercoagulability makes prosthetic valves susceptible to thrombosis. Despite appropriate management with a somatostatin analog, some patients continue to have high markers of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Similar studies were identified in our analysis, and the mitral valve was most frequently correlated with thrombosis, while the aortic valve was only involved in 15% of cases, According to previous research, this study indicated that the incidence of mitral PV thrombosis was 2-3 times greater than the frequency of aortic prosthesis. These results were consistent with those of Gupta et al 13 . that indicated that 84% of patients with mitral position had PVT episodes.…”
Section: Discussionsupporting
confidence: 94%
“…Similar studies were identified in our analysis, and the mitral valve was most frequently correlated with thrombosis, while the aortic valve was only involved in 15% of cases, According to previous research, this study indicated that the incidence of mitral PV thrombosis was 2-3 times greater than the frequency of aortic prosthesis. These results were consistent with those of Gupta et al 13 . that indicated that 84% of patients with mitral position had PVT episodes.…”
Section: Discussionsupporting
confidence: 94%
“…9 Although bioprosthetic valves allow avoidance of permanent anticoagulation, new fibrous plaques may deposit on bioprosthetic valves because of continual circulation of NET secretions and lead to eventual degeneration of the valve. 10 Although rare, plaque deposition may occur at 3 to 8 years postoperatively. 11 Median survival time after valve replacement has been estimated to be 6 to 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Slow blood flow Turbulence Incomplete apposition [80,81], Hypercoagulability [82,83], Turbulence [84,85], and Incomplete apposition [86,87] can be found through the cited sources. See [2] for a more detailed list of factors involved in prosthetic valve thrombosis.…”
Section: Mitral Valvementioning
confidence: 99%
“…Hemostatic and hemodynamic factors involved in the development of prosthetic valve thromboses. Additional information regarding Slow blood flow[80,81], Hypercoagulability[82,83], Turbulence[84,85], and Incomplete apposition[86,87] can be found through the cited sources. See[2] for a more detailed list of factors involved in prosthetic valve thrombosis.…”
mentioning
confidence: 99%